На маргінесі лінгвістичних студій: до питання про польські впливи у формулярі «руських» привілейних грамот - Геращенко, Ольга М. (Slavia Occidentalis, 2022)
The study of the links between the style of Ruthenian deeds from the second half of the 16th – the mid-17th centuries and their Polish counterparts have just been started in Ukrainian historical linguistics. This paper aims to analyse the role of Polish acts and act language in the development of certain linguistic formulas in the Ruthenian privilege deeds from the second half of the 16th – the mid-17th centuries. The sections of inscriptio, promulgatio, salutatio, sanctio, datum, and subscriptio are at the heart of the research. At the stylistic level, in Ukraine the Ruthenian privilege deeds were proved to clearly follow the Polish documents, possibly due to the expansion of the Polish documents and the language: compulsory and prestigious among educated people. The influence manifests itself in the following way: the deeds where the inscriptio has a list of addressees became typical; the promulgatio went after the inscriptio; the salutatio received Polish-like linguistic formulas and – if this section appears – there was no promulgatio; the new prohibition formulas in the sanctio as well as the absence of corroboratio and vice versa; the establishment of formula sequence in the datum as well as the fixation of three date variants (short, medium, and expanded), and the modification of the datum formulas according to the Polish pattern; the Ruthenian deed subsciptio cogenty influenced by the Polish document (inter alia, king’s Latin signatures, Polish pattern of Ruthenian signatures); the presence of some clichés (not related to certain clauses) either formed according to the Polish pattern or used in the Ruthenian acts with expansion of such patterns; the support of verbal amplification as a mean of stylistic precept.